2015
DOI: 10.1007/s10439-015-1479-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Postural Stability Entropy Analyses to Differentiate Fallers and Non-fallers

Abstract: The health and financial cost of falls has spurred research to differentiate the characteristics of fallers and non-fallers. Postural stability has received much of the attention with recent studies exploring various measures of entropy. This study compared the discriminatory ability of several entropy methods at differentiating two paradigms in the center-of-pressure (COP) of elderly individuals: 1.) eyes open (EO) versus eyes closed (EC) and 2.) fallers (F) versus non-fallers (NF). Methods were compared usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 41 publications
2
21
1
Order By: Relevance
“…The studies that evaluated static postural stability used various entropy methods, such as Shannon entropy [9,62], Renyi entropy [9,62], approximate entropy [47,51,54,62], sample entropy [51,54,55,62,63], multiscale entropy [48][49][50]53,[56][57][58][59]61,62,65], composite multiscale entropy [62], and multivariate multiscale entropy [15,56], in order to find a better approach to evaluate human posture. The findings of the previous studies comparing entropy and traditional COP methods suggested that the entropy approach is more sensitive in characterizing sway [59] and gives higher reliability [55].…”
Section: Comparison Between Entropy Methods and Traditional Copmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies that evaluated static postural stability used various entropy methods, such as Shannon entropy [9,62], Renyi entropy [9,62], approximate entropy [47,51,54,62], sample entropy [51,54,55,62,63], multiscale entropy [48][49][50]53,[56][57][58][59]61,62,65], composite multiscale entropy [62], and multivariate multiscale entropy [15,56], in order to find a better approach to evaluate human posture. The findings of the previous studies comparing entropy and traditional COP methods suggested that the entropy approach is more sensitive in characterizing sway [59] and gives higher reliability [55].…”
Section: Comparison Between Entropy Methods and Traditional Copmentioning
confidence: 99%
“…Quiet standing is the most common postural task in the postural stability studies [9,15,[47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62]. The other static postural tasks, such as the single-leg stance [59,63], tandem stance [15], and standing on a sway support [52,55,60], were used to evaluate the performance of the perturbed balance task.…”
Section: Previous Studies Based On the Postural Tasksmentioning
confidence: 99%
“…To date, only ApEn and SampEn have been reported to assess the complexity of postural stability post-concussion, but other entropy analyses may be more appropriate for COP complexity. Examining complexity over multiple timescales can improve the sensitivity to postural control changes [12]. Because COP data are multi-dimensional with anteroposterior (AP) and mediolateral (ML) components, multivariate entropy methods may also be appropriate to account for potential correlations between the directions [13].…”
Section: Introductionmentioning
confidence: 99%
“…Both approximate Entropy and sample Entropy have also been used within a multiscale Entropy framework, see Costa et al [25] where the multiple scales provide an advantage enabling the randomness or complexity of a signal to be quantified across a range of scales so that signals can be compared more easily. For example, Ramdani et al [26] and Fino et al [27] looked at posture fluctuations to compare falling in elderly people; artefact detection in electroencephalographic signals is also another popular topic e.g. Mariani et al [28]; analysis of various engineering type problems such as for two phase flow e.g.…”
Section: Introductionmentioning
confidence: 99%